Feasibility of managing and organizing the problem of informal settlements a field study on informal areas in Najaf Governorate - Alfadhel, Ali Abdulhussein Khaleel; Al-Sharifi, Zainab Hadi Maaouf; Almohammed, Firdews Abdulhussein (Edelweiss Applied Science and Technology, 2024)
The research aims to study the problem of informal housing in Najaf Governorate, present strategic scenarios to solve the problem, as well as choosing the low-cost construction strategy as an approved strategy in the research. The study included (9) areas in which informal housing units spread, namely (Al-Radhwiya, Al-Rahma neighborhood, Al-Najaf Sea depression, Al-Shawafi area, behind Al-Quds neighborhood, Al-Jadidah II slums, Al-Jadidah III slums, Tabuk neighborhood, Al-Barakiyah), affiliated to the Najaf Governorate Municipality Directorate. The researchers used the descriptive analysis method based on structured personal interviews in informal areas to identify the problem, in addition to using financial tools by calculating costs (fixed capital, working capital) and revenues to solve the problem by submitting a proposal to establish a low-cost residential complex. The study reached several conclusions, the most important of which is that efforts and procedures can be organized to reach a radical solution by choosing the optimal and fastest scenario, which is building low-cost housing units, and benefiting from the areas on which slums were built. The study recommended a set of recommendations, the most important of which is forming a government working group from the departments concerned with urban planning, the municipality, the Investment Authority, and departments related to infrastructure, to prepare a technical study and an action plan to establish a package of projects distributed across the governorate's areas. These projects are granted to the best investors in establishing low-cost housing units, and forming a subcommittee to evaluate the lands and re-use them in an optimal manner. In a way that achieves benefit for the city, whether by converting them into green spaces, parks, or investment projects that enhance commercial activity in the city.